Magnetic properties of Ba Ferrite Substituted by Low Fraction of Ni Cations : DOI : 10.48129/kjs.20239 - H. Abdel-Mohsen, Luma; H.lafta, Sadeq; Sh.Hashim, Mustafah (Kuwait Journal of Science, 2023)
Four composition of spinel Ba ferrite having the formula NixBa1-xFe2O4 with the moalr ratio of x=0, 0.05, 0.01 and 0.15. The sol-gel auto-combustion route was used to synthesize these depending on metal nitrates and citric acid followed by a firing at 600˚C. The XRD, FTIR and SEM analyses to determine the structural properties were done. All samples showed cubic spinel structure before and after firing with a noticible of FTIR tetrahedral band blue shift as the molar ratio x was increased. The crystallite size and particle size have the same behavior as x changed from 0 to 0.15 where a cleare dependence of these two parameters on Ni content. The whole samples showed a spherical nanoparticles aggregated in large clusters. Magnetic properties, as tested by VSM instrument, displayed a varying magnetization saturation Ms, that was droped an then increased as x got to its max value. A Ms of more than 48 emu/g was achieved at x=0 and x=0.15 while the coercivity did not changed clearly. The fitting by Langevin eguation using Originlab software showed a very close values of Ms to that measured by VSM test. Magnetic parameters generaly affected by the both of the composition and particle size.